“Being Yourself”: Self-Determination at a Summer Sports Camp for Youths With Visual Impairments - Lepore-Stevens, Maria; Schugar, Heather (Journal of visual impairment & blindness, 2023)
Introduction: This mixed-methods study examined self-determination at a summer sports camp for youths with visual impairments (i.e., those who are blind or have low vision). Educators of students with visual impairment have reported that the expanded core curriculum should be taught outside of the school day and have reported placing a lower priority on teaching self-determination skills during school hours. Methods: Athletes at a mid-Atlantic sports camp for youths with visual impairments responded to the American Institute for Research (AIR) Self-Determination Scale survey regarding perceptions of their own self-determination across three settings, a questionnaire about their experiences of self-determination during camp, and interviews about their understanding of self-determination at camp. Adult coaches responded to a questionnaire concerning opportunities for athletes to develop self-determination skills. Results: A repeated measures ANOVA on composite scores of AIR Self-Determination Scale across home, school, and camp settings revealed athletes were statistically significant, F(2.13) = 24.24, p < .001. Athletes were more confident in their self-determination skills at camp (M = 26.6, SD = 3.33) compared to home (M = 19.1, SD = 5.76) and school (M = 19.2, SD = 5.21). Athletes reported the camp setting allowed for the development of self-determination skills by fostering positive relationships between coaches and athletes, providing emotional support, and promoting inclusion with respect to visual impairment. Limitations included the small sample size, question comprehension, shortened data collection, busy environment, and nature of the relationship between participants and researchers. Discussion: This research will contribute to literature related to teaching self-determination skills to young people with visual impairments and has implications for classroom learning. Implications for Practitioners: Low student-to-staff ratios, access to adapted sports, options to follow one's interests throughout the day, and goal-setting are aspects of camp that educators can adopt to promote self-determination in school.